Peranan Orang Tua dalam Membentuk Karakter Religius Anak dalam Pendidikan Agama Kristen di SMAN 4 Palangkaraya - Rada Christina; Wahyunisa Wahyunisa; Restani Veronika; David Daniel Alex (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The aim of this research is to explore the role of parents in shaping the religious character of children through Christian Religious Education in the city. The type of research conducted is field research with a qualitative research model. The data sources used in this study include both primary and secondary data. The data collection methods employed are Observation, Interview, and Documentation. Data analysis is carried out through three stages: data reduction, data presentation, and drawing conclusions. The research findings indicate that parents play a crucial role in shaping the religious character of their children through several approaches. These include educating through behavioral examples, implementing an early education system, establishing a system of habituation, fostering a culture of dialogue between parents and children, and applying principles of justice in managing available time. Behavioral examples provided by parents have proven to be highly effective in guiding children to become useful individuals. For these behaviors to be truly effective, they must be supported by consistent policies applied across all aspects of daily life.